Keragaan Agronomi dan Preferensi Petani Terhadap VUB Padi Melalui Pendekatan PTT dengan Sistem Tanam Jajar Legowo di Kabupaten Dompu NTB - Sudarto, Sudarto; Hipi, Awaludin; Windiyani, Hiryana (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
An effort to increase rice production is the use of new varieties (VUB). VUB is a major technology component in the application of Integrated Crop Management (ICM). The purpose of the assessment is to look at the performance of growth and yield of paddy VUB compared with common rice varieties planted by farmers. The assessment was conducted in farmer's land in MK I (April-July 2015) in rural districts Ranggo Pajo Dompu involving four farmers, with a total land area of 1.0 ha. Assessment prepared following the randomized block design (RAK) with four replications. A total of five (5) VUB tested as a treatment : Inpari 10, Inpari 16, Inpari 19, Inpari 22, Inpari 30 Ciherang sub 1 and Cigeulis (control). In this study also apply row planting legowo system 2: 1 (spacing of 40 x 20 x 10 cm). Parameter observed among others: plant height, number of productive tiller, the number of grains / panicle, weight of 1000 seeds, dried grain yield harvest. Data were analyzed using analysis of variance (ANOVA) with the software DSAASTAT versi 1.101 and if there are differences among the treatments, it will be tested further with the Least difference significant test (LSD) at 5% level. The study showed performance of growth and yield components of new varieties (VUB) of paddy in all the observed parameters give significantly different results against paddy than varieties commonly grown by farmers (varieties Cigeulis). The results obtained at the Inpari 30 Ciherang sub 1 (5.57 t/ha GKP), followed by Inpari 19 (5.20 t/ha GKP); Inpari16 (5.43 t/ha GKP); Inpari 22 (5.20 t/ha GKP), Inpari 10 (5.19 t/ha GKP) and varieties Cigeulis (5.06 t/ha GKP). Based on the preferences of farmers Inpari 30 Ciherang sub 1 is quite unpopular compared with other varieties.